Emotion Regulation in Mexican and U.S. White Adults: Cultural and Gender Differences - Gallegos, Julia; Rodriguez, Norma; Ramirez III, Manuel; Berman, Noah Chase; Abramowitz, Jonathan (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2023)
The present study aimed to clarify the relationship between (a) cultural differences (reflected in family values and family environments) and gender and (b) cognitive reappraisal and expressive suppression among Mexican and White U.S. undergraduate college students. The Emotion Regulation Questionnaire (ERQ) to assess Cognitive Reappraisal and Expressive Suppression; the Family Environment Scale (FES) to assess Cohesion, Conflict, and Expressiveness within the family environment; the Family Attitude Scale (FAS) to assess traditional values; and a demographic questionnaire were completed by 337 participants from Mexico (267 women, 70 men) and 192 White participants from the U.S. (108 women, 83 men, and 1 nonbinary-identified adult). Mexican respondents scored statistically significantly higher on Cognitive Reappraisal than did U.S. participants. Mexicans also scored statistically significantly lower on the Conflict and Expressiveness subscales of the FES. Regression analyses showed that higher scores on Cohesion and lower scores on Expressiveness among Mexicans were related to higher scores on Cognitive Reappraisal and lower scores on Expressive Suppression. Women in both countries scored statistically significantly lower on Expressive Suppression and higher on Cognitive Reappraisal than did men. These findings highlight how specific cultural, familial, and gender factors predict critical emotion regulation processes. Recommendations for future research and intervention are discussed.